Faktor yang Berhubungan dengan Penggunaan Kondom pada ‘Lelaki Seks Lelaki’ di Komunitas Independent Men Of Flobamora Kota Kupang - Julia C. Polly; Pius Weraman; Sigit Purnawan (Universitas Nusa Cendana, 2021)
One of the populations at risk of HIV-AIDS is Men Sex with Men (MSM) because of unsafe sexual behavior, namely through anal and oral sex. One of the preventions of HIV-AIDS in MSM is the consistent use of condoms every time they have sex. There are various factors that influence the use of condom. This study aims to analyze various factors associated with condom use in MSM in the IMOF Community to prevent HIV-AIDS in 2020. The research’s design is a quantitative with a cross-sectional study design. The sampling method was carried out by simple random sampling technique and the sample size was 96 MSM with a questionnaire as the instrument. Data were analyzed using Chi-Square. The results showed that there was a relationship between knowledge (ρ = 0.002), attitude (ρ=0.000), information exposure (ρ=0.042), availability of condoms (ρ=0.022), partner support (ρ=0.000) and support from friends in the community (ρ=0.009) with the use of a condom. From this study, it can conclude that knowledge, attitudes, information exposure, availability of condoms, support from partners, and support from friends in the community are a factor that influences condom use among MSM in the IMOF Community in Kupang City in preventing HIV-AIDS. It hoped that MSM could maintain and increase their knowledge, actively seek information about HIV-AIDS, independently provide condoms to be used, strengthen relationships with partners and friends in the community to help in HIV-AIDS prevention efforts.